Pinniped response to diadromous fish restoration in the Penobscot River Estuary - Leach, Lauri; Stevens, Justin R.; Cammen, Kristina (Frontiers in Conservation Science, 2024)
Successful conservation of pinnipeds in the northwest Atlantic has led to increasing populations of harbor seals (Phoca vitulina) and gray seals (Halichoerus grypus) in the Gulf of Maine. Within this region, habitat restoration and diadromous fish conservation in the Penobscot River have also been top priorities for the past decade. To understand the overlap between the regional recovery of pinnipeds and the aggregative response of pinnipeds to increasing forage fish, we assessed how counts, distribution, and behavior of seals in the Penobscot River Estuary have changed over time from 2012 to 2020 and determined whether those changes were related to changes in fish biomass that are occurring as the result of diadromous fish restoration. We did not see increased counts of hauled-out seals, but consistent with regional harbor seal phenology, hauled out seal counts were highest in late spring and declined throughout the summer and into the fall. The number of swimming harbor and gray seals, analyzed as a proxy for changes in behavior, showed a stronger annual trend with an increase throughout the study period. Fish biomass was negatively associated with total number of hauled out seals and swimming gray seals but positively associated with swimming harbor seals. We also documented the potential displacement of harbor seals when gray seals are present. Together, these results begin to provide insights into how regional conservation and local restoration efforts interact to affect multiple trophic levels in an ecosystem. Continued monitoring of predator-prey interactions, along with diet and movement studies, will further elucidate seal aggregative response to increasing prey species in this system and the potential impact of recovering predator populations on restored prey populations. Knowledge gained regarding pinniped response to increasing fish biomass has important implications for other systems with ongoing conservation measures that aim to improve habitat, decrease exploitation, or recover protected species. Studies like these can be critical for finding paths forward to reconcile the potentially competing objectives of marine mammal protection and fish restoration.